2008
DOI: 10.1016/j.chemosphere.2007.07.056
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale analysis of heavy metal contents in Spanish agricultural topsoils

Abstract: This study characterized and mapped the spatial variability patterns of seven topsoil heavy metals (Cr, Ni, Pb, Cu, Zn, Hg and Cd) within the Ebro river basin (9.3 million ha) by Multivariate Factorial Kriging. The variograms and cross-variograms of heavy metal concentrations showed the presence of multiscale variation that was modeled using three variogram models with ranges of 20 km (short-range), 100 km (medium-range) and 225 km (long-range). Our results indicate that the heavy metal concentration is influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(65 citation statements)
references
References 44 publications
(37 reference statements)
11
54
0
Order By: Relevance
“…Numerous investigations have focused on the total heavy metal concentrations in Pb-Zn mining areas [15][16][17][18][19][20]. However, more comprehensive investigations including spatial variation, vertical distribution, and risk assessment of heavy metals in soil from the abandoned Pb-Zn mining area were rarely documented.…”
mentioning
confidence: 99%
“…Numerous investigations have focused on the total heavy metal concentrations in Pb-Zn mining areas [15][16][17][18][19][20]. However, more comprehensive investigations including spatial variation, vertical distribution, and risk assessment of heavy metals in soil from the abandoned Pb-Zn mining area were rarely documented.…”
mentioning
confidence: 99%
“…Comparing the range of As and metals, it was found that Cd and Pb have longer effective ranges than As and the other metals, which indicates that Cd and Pb have better spatial structure and less variation caused by extrinsic factors. Human activities have effects on only short and medium-range scales of variation (Rodríguez Martín et al, 2008). In this study, semivariograms of Cr, Cu and Zn are dominated by short-range structure, and the semivariogram of As and Ni are of medium-range variation.…”
Section: Spatial Analysis 331 Geostatistical Analysismentioning
confidence: 90%
“…The significant positive correlation between Cd, Cu, Zn and Ni is consistent with a common source for these metals. Associations among these metals can be indicative of sources due to human activities or geogenic and pedogenic characteristics (Facchinelli et al, 2001;Rodríguez Martín et al, 2008). As and Pb were significantly negative correlated to Cd, Cu, Zn and Ni.…”
Section: Discussionmentioning
confidence: 99%
“…Pb would originate principally from the gases emitted by vehicles) or natural causes (Facchinelli et al, 2001;Nicholson et al, 2003;Micó et al, 2006;Rodríguez et al, 2008;Sheppard et al, 2009).…”
Section: Introductionmentioning
confidence: 99%